Fluidised Bed Reactors for the Thermochemical Conversion of Biomass and Waste - Stefano Iannello; Shane Morrin; Massimiliano Materazzi (KONA Powder and Particle Journal, 2019)
The growing population and economic development globally has led to increasing resource consumption and waste generation. This has generated concern at local, national and international levels on environmental issues including air quality, resource scarcity, waste management (including plastics) and global warming. The resulting antipathy towards fossil fuels and waste landfilling has spurred the demand for alternative bioenergy and biofuels production methods, making use of abundant biomass and waste feedstock. Although not new concepts, there has been renewed impetus recently to develop advanced thermochemical processes such as pyrolysis and gasification to treat biomass and municipal solid waste (including refuse-derived fuel therefrom). This is because these processes have the potential to add value to cheap and abundant materials by converting them into advanced biofuels and chemicals. The work presented in this paper is concerned principally with the technical analysis and review of new-generation, state-of-the-art systems based on fluidised bed reactors operated with biomass and solid waste. A comprehensive assessment of fluidised bed reactor types and operations is considered, with particular attention given to those processes aimed at the production of clean syngas for the subsequent synthesis of high-value products, including bio-hydrogen, synthetic natural gas (SNG), and liquid fuels.